Analisis Tingkat Kecemasan Atlet Ekstrakurikuler Bola Voli SMA Negeri Balung - Muzakhi, Gibran; Hardovi, Bahtiar Hari; Apriliyanto, Rizki (Universitas Hamzanwadi, 2025)
Anxiety is a psychological challenge that can affect athlete performance, especially at the student level in extracurricular activities. This study aims to analyze the level of anxiety of volleyball extracurricular athletes at SMA Negeri Balung. The method used is descriptive quantitative with a survey approach. The sample amounted to 20 athletes, taken using purposive sampling technique. The research instrument was a questionnaire based on the Sport Anxiety Scale-2 (SAS-2) with 15 questions covering three phases of anxiety: before, during, and after competition. Data were collected during routine training sessions and analyzed using percentage-based quantitative descriptive techniques. The results showed that anxiety appeared significantly in all three phases. The pre-competition anxiety level was 18%, with anxiety dominated by nervous feelings, negative thoughts, and low self-confidence. The percentage of anxiety during the match reached 26%, there was tension, fear of making mistakes, and physical symptoms such as trembling. The highest anxiety actually appears after the match, with a percentage of 39%. anxiety develops into negative reflections and emotional distress. This study concludes that athlete anxiety is multidimensional and sustainable, so comprehensive mental coaching is needed in extracurricular activities.